Increasing adult ICU nurse's bioethical knowledge on death and dying - Olguera, Ana Macapanas
Death education programs for health professionals, whose work involves "the laying of hands" and making decisions of a life-death nature, is more intricate than any other death education programs. Ideally, death education programs intended for nurses and physicians must be build upon a sound basic education on death and dying and more importantly, strong bioethical principles which would guide healthcare professionals in making sound bioethical decisions.In this light, this study was conducted to determine the cognitive level of ICU nurses on care of death and dying patients before and after instituting bioethical teaching program related on this topic and to ascertain the relationship of the following variables (age, civil status, length of service and personal experience of death) with the nurses' bioethical knowledge on care of death and dying patients.The study utilized quasi-experimental design specifically pretest-posttest model. It was conducted in two adult Intensive Care Units namely Medical ICU and Central ICU. Thirty-three nurses who have met the set inclusion criteria were included in this study.A 30-item questionnaire was given to all nurse participants. The questionnaire included our hypothetical cases that described clinical situations that needed decisions to presented bioethical dilemma. Questions involved the entire major groups of bioethical principles namely maximize good, respect for person and justice. The said questionnaire was given twice. Pretest was given initially and then after two weeks, bioethical teaching program was given. After another two weeks, the same set of questionnaire was given again as posttest.